Lingaoamide, a cyclic heptapeptide from a Chinese freshwater cyanobacterium Oscillatoria sp. (6th July 2021) - Iwasaki, Arihiro; Kurisawa, Naoaki; Wang, Tingting; Li, Xiaohui; Luo, Haixi; Zhu, Chengcong; Patial, Gaurav; Yan, Xiaojun; He, Shan; Luzzatto-Knaan, Tal; Tian, Fuli; Naman, C. Benjamin; et al.
Graphical abstract: Highlights: Cyanobacteria were collected from flooded paddy farm fields in Hainan, China. A new marine natural product, lingaoamide, was discovered and characterized. Lingaoamide upregulates biogenesis of pro-pathogenic melanins in rice blast fungus. Lingaoamide does not appear to modulate plant growth or immune response. Abstract: Lingaoamide (1 ), a new cyclic heptapeptide natural product, was isolated from a freshwater Oscillatoria cyanobacterium. The producing organism was collected in Chinese water spinach paddy farm fields in Lingao County, Hainan, China. The structure of 1 was determined by conventional mass spectrometry, NMR spectroscopy, and chemical degradation studies. Lingaoamide concentration-dependently up-regulates the biogenesis of pro-pathogenic melanin pigments (melanogenesis) in the rice blast fungus, Magnaporthe grisea, when tested in vitro . This molecule also exhibits weak in vitro inhibition (MIC 32 μg/mL) of Gram-negative Pseudomonas aeruginosa and Gram-positive Bacillus pumilus, and does not appear to impact plant growth or immune response in vivo using the model organism, Arabidopsis thaliana .